2006
DOI: 10.1186/1471-2407-6-220
|View full text |Cite
|
Sign up to set email alerts
|

CA 15-3 is predictive of response and disease recurrence following treatment in locally advanced breast cancer

Abstract: Background: Primary chemotherapy (PC) is used for down-staging locally advanced breast cancer (LABC). CA 15-3 measures the protein product of the MUC1 gene and is the most widely used serum marker in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 18 publications
3
39
1
1
Order By: Relevance
“…In the current study, outcome was favorable in patients with negative hormonal receptor status or HER2 overexpression following chemotherapy for breast cancer, consistent with previous studies [25,26,28]. However, other studies have found no association with treatment response [27,29]. These discordant results may be due to the small number of patients, the heterogeneous patient populations and chemotherapy regimens analyzed as well as differing selection criteria.…”
Section: Discussioncontrasting
confidence: 31%
“…In the current study, outcome was favorable in patients with negative hormonal receptor status or HER2 overexpression following chemotherapy for breast cancer, consistent with previous studies [25,26,28]. However, other studies have found no association with treatment response [27,29]. These discordant results may be due to the small number of patients, the heterogeneous patient populations and chemotherapy regimens analyzed as well as differing selection criteria.…”
Section: Discussioncontrasting
confidence: 31%
“…In breast cancer the role of serum markers is less well established [1][2][3]. The elevation of serum markers in breast cancer may be helpful in early diagnosis, determining prognosis, predicting response or resistance to specific therapies, surveillance after primary surgery, and monitoring therapy in patients with advanced disease [4][5][6]. Breast cancer is a heterogenic disease and none of the available markers is increased in all patients with breast cancer even in an advanced stage of the disease [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Understandably, because of its abundant expression and remarkable relevance to the development of the pathology, MUc-1 is the most widely used serum marker for breast cancer (1).…”
Section: Imaging Target-umuc-1 Tumor Antigenmentioning
confidence: 99%
“…As a molecule directly involved in cell adhesion and proliferation, it is not surprising that MUc-1 expression is highly correlated with both tumor growth and metastatic potential, making it an important predictive marker not only for the transition from early to locally advanced disease but also for the progression to advanced malignancy (57,66,75,89). in addition to being an excellent marker for the prediction and characterization of tumor progression, MUc-1 availability is also directly related to treatment outcome, making this target antigen one of the most widely used markers of therapeutic response and disease recurrence, particularly in patients with locally advanced and invasive disease (1). in patients treated with neoadjuvant chemotherapy, MUC-1 levels were found to be consistently reduced, suggesting that MUc1 can be explored as an intermediate biomarker for assessment of treatment and prognosis (27).…”
Section: Imaging Target-umuc-1 Tumor Antigenmentioning
confidence: 99%